2020
DOI: 10.1093/ehjci/jeaa010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of energy loss index in patients with low-gradient severe aortic stenosis and preserved ejection fraction

Abstract: Aims  We hypothesized that among patients with low-gradient severe aortic stenosis (AS) and preserved left ventricular ejection fraction (LVEF), reclassification of AS severity as moderate by pressure recovery adjusted indexed aortic valve area (AVAi) = energy loss index (ELI), may identify a subgroup of patients with a better outcome. Methods and results  Three hundred and seventy-nine patients with low-gradient AS (defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Altes et al described a 39% reclassification rates from severe to moderate with a two-fold risk reduction of cardiac events during their follow up. 13 Similar findings where described by Heo et al with 45% of the patients initially classified as low-gradient severe AS were reclassified as having moderate AS. 12 Multimodal imaging approaches have also been employed, with one study using multidetector computed tomography and Doppler Echocardiography measurement of the LVOT resulting in the reclassification of 43% of the patients from severe AS to moderate AS using ELCO.…”
supporting
confidence: 79%
“…Altes et al described a 39% reclassification rates from severe to moderate with a two-fold risk reduction of cardiac events during their follow up. 13 Similar findings where described by Heo et al with 45% of the patients initially classified as low-gradient severe AS were reclassified as having moderate AS. 12 Multimodal imaging approaches have also been employed, with one study using multidetector computed tomography and Doppler Echocardiography measurement of the LVOT resulting in the reclassification of 43% of the patients from severe AS to moderate AS using ELCO.…”
supporting
confidence: 79%
“… 11 Compared with the present study, Altes et al included symptomatic patients, and patients with a number of comorbidities, including history of atrial fibrillation in 40%, chronic renal failure in 32%, and diabetes mellitus in 36% of patients. 11 …”
Section: Discussionmentioning
confidence: 84%
“…10 Previous studies have demonstrated the prognostic value of pressure recovery adjusted valve area (energy loss (EL)) indexed for body surface area in AS. 9 Use of EL index rather than AVA index reduced the prevalence of asymptomatic severe AS in the large Simvastatin Ezetimibe in Aortic Stenosis (SEAS) study 8 as well as the phenomenon of DGAS in symptomatic patients, as recently demonstrated by Altes et al 11 Recent publications have questioned the value of indexing AVA to body surface area. 12 It is also well demonstrated that both very small and very large body surface area in itself is associated with worse prognosis.…”
Section: What This Study Addsmentioning
confidence: 94%
“…This apparent discrepancy requires further physiologic and fluid dynamic consideration. Firstly, by calculating the energy loss index of these severe AS patients with normal LVEF based on routine echo assessment, Altes et al [79] reported that up to 40% of cases could be reclassified from severe into moderate AS, thus no longer requiring immediate surgical intervention. Secondarily, the LF-LG AS is frequently associated with systemic hypertension, which is known to have a major impact on the hemodynamic performance of the stenotic aortic valve and left ventricle.…”
Section: Effects Of Pacemaker and Bundle Branch Block On LV Remodelling And Outcomementioning
confidence: 99%